2009
DOI: 10.1105/tpc.108.060145
|View full text |Cite
|
Sign up to set email alerts
|

AnArabidopsisGPI-Anchor Plasmodesmal Neck Protein with Callose Binding Activity and Potential to Regulate Cell-to-Cell Trafficking

Abstract: Plasmodesmata (Pds) traverse the cell wall to establish a symplastic continuum through most of the plant. Rapid and reversible deposition of callose in the cell wall surrounding the Pd apertures is proposed to provide a regulatory process through physical constriction of the symplastic channel. We identified members within a larger family of X8 domaincontaining proteins that targeted to Pds. This subgroup of proteins contains signal sequences for a glycosylphosphatidylinositol linkage to the extracellular face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
278
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(304 citation statements)
references
References 76 publications
10
278
0
4
Order By: Relevance
“…In leaves, CML41‐GFP localizes to punctate spots at the cell periphery (Fig. 2a–c), patterning that is reminiscent of plasmodesmata (Thomas et al ., 2008; Simpson et al ., 2009). We confirmed CML41‐GFP was localized to plasmodesmata by co‐staining plasmodesmal callose in Arabidopsis with aniline blue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In leaves, CML41‐GFP localizes to punctate spots at the cell periphery (Fig. 2a–c), patterning that is reminiscent of plasmodesmata (Thomas et al ., 2008; Simpson et al ., 2009). We confirmed CML41‐GFP was localized to plasmodesmata by co‐staining plasmodesmal callose in Arabidopsis with aniline blue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several other works noted additional internal substructures (Ding et al 1992b, Overall and Blackman 1996. Recently, PD-associated proteins have been identified in charophycean algae and land plants , Blackman and Overall 1998, Gestel et al 2003, Faulkner et al 2005, Sagi et al 2005, Thomas et al 2008, Simpson et al 2009, Faulkner and Maule 2010. These works suggested that there are highly complicated control mechanisms underlying the cell-to-cell molecular traffic via PD.…”
Section: Introductionmentioning
confidence: 98%
“…Actin filaments associated with the desmotubule structure within the PD are believed to play a role in regulating the aperture of the cytoplasmic sleeve between the PM and desmotubule (Ding et al, 1996;Su et al, 2010). In addition, GPIanchored protein PDCB1 is also located in the PD structure and impacts PD function (Simpson et al, 2009). Overexpression of PDCB1 resulted in increased callose accumulation and changes in PD conductivity (Simpson et al, 2009).…”
Section: Gsd1 Controls Photoassimilate Translocation Through the Sympmentioning
confidence: 99%
“…Callose deposition can also impact the size of the PD aperture at the neck region (Radford et al, 1998;Levy et al, 2007) and callose synthase genes such as Glucan SynthaseLike7 (GSL7, also named CalS7), GSL8, and GSL12 have been shown to play a role in regulating symplastic trafficking (Guseman et al, 2010;Barratt et al, 2011;Vatén et al, 2011;Xie et al, 2011). Other proteins that have been shown to impact the structure and function of the PD include glycosylphosphatidylinositol (GPI)-anchored proteins, PD callose binding protein1 (PDCB1), which is also associated with callose deposition (Simpson et al, 2009), and LYSIN MOTIF DOMAIN-CONTAINING GLYCOSYLPHOSPHATIDYLINOSITOL-ANCHORED PROTEIN2, which limits the molecular flux through the PD by chitin perception (Faulkner et al, 2013). Changes in PD permeability can have major consequences for the translocation of photoassimilates needed for grain filling in rice.…”
mentioning
confidence: 99%
See 1 more Smart Citation